Social moderation, assessment and assuring standards for accounting graduates - Watty, K.; Freeman, M.; Howieson, B.; Hancock, P.; O'connell, B.; De Lange, Paul; Abraham, A. (Routeledge, 2014)
Evidencing student achievement of standards is a growing imperative worldwide. Key stakeholders (including current and prospective students, government, regulators and employers) want confidence that threshold learning standards in an accounting degree have been assured. Australia’s new higher education regulatory environment requires that student achievements are benchmarked against intended programme learning outcomes, guided by published disciplinary standards and a national qualifications framework, and against other higher education providers. Here, we report on a process involving academics from 10 universities, aided by professional practitioners, to establish and equip assessors to reliably assure threshold learning standards in accounting that are nationally comparable. Importantly, we are learning more about how standards are interpreted. Based on the premise that meaning is constructed from tacit experiences, social interactions and intentional reflection on explicit information, we report outcomes of three multi-part calibration interventions, situated around judgements of the quality of the written communication skills exhibited in student work and their related assessment tasks. Qualitative data from 30 participants in the calibration process suggest that they perceive that the process both assists them both in developing a shared understanding of the accounting threshold learning standards and in the redesign of assessment tasks to more validly assess the threshold learning standards.